Successful Management of Pregnancy in Patient with Severe Morbid Obesity - Z Basirat, (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Morbid or extended obesity (class III) is uncommon in pregnancy and associated with higher rates of pregnancy complications compared to women with normal weight. In this report, a successful management of pregnancy in patient with severe morbid obesity with weight 175kg and overt diabetes and chronic hypertension was introduced.CASE: A 31-year-old pregnant woman with history of overt diabetes and hypertension with weight 175kg and a body mass index of 64 kg/m2 was admitted to Ayatollah Roohani hospital of Babol, Iran. Her diabetes and hypertension well controlled. She was scheduled for a cesarean section (C/S) at 37 gestational weeks. Spinal anesthesia and C/S by Pfannenstiel incision was applied for this patient. Delivery outcome was a healthy female neonate with 3300 gr weight and Apgar score of 9-10. The mother was discharged with good condition. There were no complications at 4-month follow-up after surgery and the patients hypertension was controlled and need for insulin decreased. CONCLUSION: Because of high maternal and fetal neonatal complications in morbid obesity, we consider good prenatal care for her medical problems and appropriate timed fetal well being test.